Developing a conceptual framework for evaluating the effects of Self-Regulated Learning (SRL) strategies on students online learning satisfaction - Lim, Chee Leong; Ab Jalil, Habibah; Ma'rof, Aini Marina; Saad, Wan Zuhainis (Asia Pacific Institute of Advanced Research, 2019)
Self-regulated learning (SRL) is one of the most important learning strategies in the context of online learning as it is required even more as compared to a face-to-face setting. Since online courses rely more exclusively upon SRL strategies, the effects of SRL and online learners’ satisfactions need to be extensively and quantitatively examined. However, a holistic study assessing the relationship between SRL strategies and students’ satisfaction in virtual learning environments is currently largely unavailable. Therefore, this study integrates SRL strategies through the lens of the Cybergogy for Engaged Learning Model to investigate students’ online learning satisfaction. Specifically, a conceptual model is developed to establish a synergy between SRL and Cybergogy to represent an appropriate synergistic framework for the implementation of the educational technologies model in the virtual learning environment. The finding is expected to contribute to the development of an evidence-based model for continuous improvement of online courses. It will also yield a more comprehensive picture of SRL in various online learning environments and serve as an guideline for universities in redesigning online courses to reforms in the era of Industrial Revolution 4.0.